Polymer:Nonfullerene Bulk Heterojunction Solar Cells with Exceptionally Low Recombination Rates. Issue 22 (1st September 2017) - Gasparini, Nicola; Salvador, Michael; Heumueller, Thomas; Richter, Moses; Classen, Andrej; Shrestha, Shreetu; Matt, Gebhard J.; Holliday, Sarah; Strohm, Sebastian; Egelhaaf, Hans‐Joachim; Wadsworth, Andrew; Baran, Derya; et al.
Abstract: Organic semiconductors are in general known to have an inherently lower charge carrier mobility compared to their inorganic counterparts. Bimolecular recombination of holes and electrons is an important loss mechanism and can often be described by the Langevin recombination model. Here, the device physics of bulk heterojunction solar cells based on a nonfullerene acceptor (IDTBR) in combination with poly(3‐hexylthiophene) (P3HT) are elucidated, showing an unprecedentedly low bimolecular recombination rate. The high fill factor observed (above 65%) is attributed to non‐Langevin behavior with a Langevin prefactor (β/βL ) of 1.9 × 10 −4 . The absence of parasitic recombination and high charge carrier lifetimes in P3HT:IDTBR solar cells inform an almost ideal bimolecular recombination behavior. This exceptional recombination behavior is explored to fabricate devices with layer thicknesses up to 450 nm without significant performance losses. The determination of the photoexcited carrier mobility by time‐of‐flight measurements reveals a long‐lived and nonthermalized carrier transport as the origin for the exceptional transport physics. The crystalline microstructure arrangement of both components is suggested to be decisive for this slow recombination dynamics. Further, the thickness‐independent power conversion efficiency is of utmost technological relevance for upscaling production and reiterates the importance of understanding material design in the context of low bimolecular recombination. Abstract : Nonfullerene‐based organic solar cells with an unprecedentedly low bimolecular recombination rate are presented. The absence of parasitic recombination and high carrier lifetimes in the devices inform an almost ideal bimolecular recombination behavior with a Langevin prefactor (β/βL ) of 1.9 × 10 −4 . This exceptional recombination behavior allows the fabrication of solar cells with layer thicknesses up to 450 nm without significant performance losses.